Diagnóstico del manejo Agrotécnico, con orientación agroecológica en la Finca “Ordóñez” Barrio Muchime, cantón Yacuambi, Zamora Chinchipe - Morales Carrión, Tatiana Rosario (2024)
The present investigation aims to diagnose the agrotechnical management with an agroecological orientation in the farm "Ordoñez" Muchime neighborhood, Yacuambi canton, Zamora Chinchipe, in order to determine which are the agrotechnical practices used in the farm for the cultivation of agricultural products. For this, a qualitative methodology of a descriptive nature was used, through which research instruments such as the interview, observation form and SWOT analysis were applied, carrying out their respective analysis, obtaining as main result that it maintains an efficient and controlled plan to protect the soil and crops, despite this, it presents certain inadequacies such as little training in marketing and commercialization strategies, soil erosion, shortage of qualified labor, as well as limited financial resources. With these results, it is concluded that the "Ordoñez" farm uses sustainable agrotechnical management that improves the quality of crops through practices that demonstrate a strong commitment to sustainability and ecosystem protection, however, certain adjustments are necessary. Based on the study, it is recommended to propose an agrotechnical management plan with an agroecological approach for the "Ordoñez" farm, which includes specific recommendations to improve agricultural sustainability and productivity, a proposal that makes it possible to reinforce and strengthen already established techniques, with the aim of effectively improving the productive performance of the farm and ensuring long-term sustainability. In this sense, the present research focuses on carrying out an extended analysis of the most relevant aspects of agrotechnical management and its most relevant techniques to end with a proposal that allows mitigating the negative effects of external factors, reducing economic and crop losses and even reducing the risk of erosion and loss of soil nutrients and, in the same way, allows maintaining relevance in economic profitability.